Galilean-newtonean rebuttal to einstein's relativity theory - Gruyitch, Lyubomir T (New Delhi : Viva Books, 2015)
The book discovers a number of the inconsistences, mistakes and paradoxes of Einstein`s relativity theory. The book presents the proofs that Einstein`s claims (lifted to the level of uncontested postulates) on the relativity of time itself, on the existence of several times and the time speeds, on the time dependence on space (frames), on the invariance of the light speed are wrong and physically meaningless. The book discovers Einstein`s tacit assumptions accepted a priory , which form the basis for all his mathematical results. The book explains and shows that all the assumptions are inacceptable, which makes all his mathematical results formally valid only under such assumptions and that his theory represents from the formal mathematical view point exclusively a singular case.
Appendices 313-346p.; Indexes 347-376p.; Bibliography 273-312p.
Keywords: General rebuttals; Time relativity; Paradoxes